2021
DOI: 10.1136/bmjopen-2020-044077
|View full text |Cite
|
Sign up to set email alerts
|

Disability status and multi-dimensional personal well-being among adolescents in the Southern Highlands Region of Tanzania: results of a cross-sectional study

Abstract: ObjectiveExamine how disability status among adolescents is associated with the following domains of personal well-being: schooling, livelihoods, health, violence and psychosocial well-being. It is hypothesised that adolescents with a disability will have greater deficits in these areas of well-being compared with their healthier counterparts.DesignCross-sectional data from 2018 were obtained from the second round of an on-going study of adolescents living in poor households in two regions of the Southern High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, those with disabilities in Tanzania often have limited knowledge of services available for treating their condition or live in rural areas where services are inaccessible. Children with disabilities are less likely to attend school; adolescents with disabilities are more likely to report poorer health status, symptoms of depression, emotional abuse, and physical violence; and adults with disabilities are less likely to be literate or married (Kuper et al, 2015; Quinones et al, 2021). Individuals with disabilities also face additional obstacles to employment, including negative attitudes, barriers to transportation, and health challenges (Morwane et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, those with disabilities in Tanzania often have limited knowledge of services available for treating their condition or live in rural areas where services are inaccessible. Children with disabilities are less likely to attend school; adolescents with disabilities are more likely to report poorer health status, symptoms of depression, emotional abuse, and physical violence; and adults with disabilities are less likely to be literate or married (Kuper et al, 2015; Quinones et al, 2021). Individuals with disabilities also face additional obstacles to employment, including negative attitudes, barriers to transportation, and health challenges (Morwane et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study on disability status and multi-dimensional personal well-being among adolescents in the southern highlands region of Tanzania reported that access to healthcare services for PWPDs continued to be a challenge in the rural area. However, the Tanzanian government has to increase its budget by 35% to rescue the situation (Quinones et al, 2021). Factors that hinder the availability of appropriate healthcare for PWPDs are unaffordability of healthcare and high transport costs, inadequate drugs or equipment, and inadequate skills of healthcare providers (Greenwood et al, 2016b).…”
Section: Satisfaction Of Healthcare Services For Pwpdsmentioning
confidence: 99%